Religion, Morality, and Democracy in Ghana - Haynes, Jeffrey (Journal of religion in Africa, 2025)
Many Ghanaians express concern about what they regard as a serious decline in morality and integrity, at both elite and popular levels. The decline is believed to fuel corruption, undermine national development, and diminish faith in democracy as the best available system of government. The paper argues that a close relationship between Ghana’s largest church, the Church of Pentecost (CoP), and the country’s two main political parties, the New Patriotic Party and the National Democratic Congress, threatens Ghana’s secular constitution and the country’s three decades of democracy in two ways. First, the CoP wants undemocratically to impose a framework to control Ghanaians’ moral behaviour according to the church’s values and beliefs. Second, the CoP’s influence on Ghana’s two main political parties seeks to prioritise power and control over all Ghanaians regardless of their religious affiliation and of the country’s commitment to democratic norms and institutions.